Efficacy of Oral Zinc Sulphate in Patients of Acne Vulgaris: Oral Zinc Sulphate in Patients of Acne Vulgaris - Javed, Mahwish; Mukhtar, Rabia; Qamar, Muneeza; Nusrat, Wajeeha; Aqeel, Ayesha; Rashid, Tariq (Pakistan Journal of Health Sciences, 2025)
Acne is a chronic condition that affects pilosebaceous units, which manifest as either inflammatory or non-inflammatory lesions. Objective: To determine the efficacy of oral zinc sulphate in patients with acne vulgaris. Methods: An observational study was held at the OPD Department of Dermatology, Jinnah Hospital-Lahore, Pakistan, which enrolled 93 patients. The Global Acne Grading System was used to evaluate acne severity. These patients were given oral zinc sulphate 220mg twice a day for 3 months. Efficacy of treatment was labelled if there was ≥50% reduction in the baseline GAGS score at the end of 3 months of treatment. All the data were processed by SPSS version 26.0. Frequency and percentages were used for categorical parameters. The chi-square test was applied, in which a p-value<0.05 was considered significant. Results: It involved cheeks and nose in 26 (28.0%) patients, followed by forehead and chin in 23 (24.7%) patients. Efficacy of treatment was observed in 53 (57.0%) patients. An insignificant difference in the frequency of efficacy across various subgroups was observed. The percent reduction in mean GAGS score from baseline ranged from 25.0% to 75.0%, with a mean of 51.2 ± 11.9%, with a significant p-value of 0.001*. There was a statistically insignificant difference in the frequency of efficacy across various subgroups based on patients’ age, gender and severity (p-value=0.870) of disease and baseline GAGS score (p-value=0.993). Conclusions: It was concluded that almost 57% of patients with mild to moderate acne showed improvement in their disease progression with oral zinc sulphate treatment. It was cost-effective with easy availability.